High-performance carbon-capturing lignocellulosic hydrochar with post-synthesis addition of spent mushroom substrate - Almeida Moreira, Bruno Rafael de [UNESP]; da Silva Alves, Lucas [UNESP]; Noble, Ralph; Zied, Diego Cunha [UNESP] (Springer Nature, 2022)
Porous carbons can capture gases and vapors from the surroundings onto their structures through either physisorption or chemisorption. However, they eventually cannot effectively bind the adsorbate to their surfaces, driving the need for introducing affinitive or selective additives into the process to improve scalable functionality. We therefore investigated whether an agro-food residue, spent mushroom substrate (SMS), would allow for developing high-throughput physisorption of CO2 on lignocellulosic hydrochar. We carbonized pinewood sawdust at 180°C and 1.5 MPa to produce the hydrochar and then mixed it with types of SMS, namely, paddy straw, grassy straw, and peaty compost, at a concentration of 1% (dry mass basis) for pelletization. We compacted 1.5-kg samples into cylindrical pellets in an automatic hydraulic piston presser machine at 100 MPa and 150°C. We obtained evidence for SMS enhancing the technical performance of the conceptual models for carbon-capturing biocarbon. For instance, the peaty compost SMS brought higher quantities of N and S to the matrix, allowing it to adsorb CO2 at 6.9±0.1 mmol g−1 at 25°C, compared with 4.3±0.2 mmol g−1 for the reference; hence, the peaty compost SMS increased the statistic adsorptive capacity of the microporous hydrochar by 38.4%. Paddy straw and grassy straw SMS also increased the adsorption to 5.2±0.2 and 5.1±0.1 mmol g−1, respectively. We therefore developed eco-friendly additives for high-performance carbon-capturing biocarbon. Our solution to physisorption offers a sustainable method of decarbonizing industrial waste streams at a higher rate than would be achievable through conventional adsorbers.
Keywords: Carbon dioxide; Hydrothermal carbonization; Physical adsorption; Porous carbonaceous matrix; Waste-to-carbon pathway